Voices of Students: We are Here! We are Ready to Care for the Next Generations! “Gathering & Sharing Wisdom Conference” and the Indigenous Child Welfare Research Network - Green, Jacquie; Taylor, Rebecca; Larken, Rakiva; Brier, Margaret; Good, Trevor (First Peoples Child & Family Review, 2010)
This paper highlights the voices of four youth presenters at the first "Gathering and Sharing Conference" hosted onCoast Salish Territory, Songhees and Esquimalt, in Victoria, British Columbia. You will be guided through story about our role as leaders, planners, and facilitators for this conference which was convened to provide a central space for Indigenous youth and other community members to share stories about the caring and nurturing of our children, families and communities.